Metabolic stress and the contractility of isolated rat myometrium: Role of potassium channels and different cellular pH buffers? - Serhatlio?lu, Ihsan; Özcan, Mete; Kutlu, Selim; Ayar, Ahmet (Turkiye Klinikleri, 2007)
Objective: The aim of this study was lo investigate the role of different pH buffers, cellular energy sources and role of potassium channels in potassium cyanide (KCN)-induced metabolic stress-mediated inhibition of contractility of isolated rat myometrium. Material and Methods: Myometrial strips were isolated from virgin adult Wistar rats after cervical dislocation and suspended in an isolated tissue bath containing Krebs solution, continuously bubbled with 95% O2 and 5% CO2, maintained at 37°C (pH 7.4). After the development of spontaneous contractions following equilibrium under resting tension, KCN, pyruvate, glybenclamide or tetra ethyl ammonium (TEA) was added to the tissue bath. The amplitude and frequency of contractions were evaluated by 10-min intervals. Wilcoxon rank test was used for statistical analysis of data. Results: KCN (0.5 mM) gradually inhibited the spontaneous contractions, being more effective in experiments where NaHCO3 was used in the Krebs solution instead of HEPES. This inhibition was reversed by pyruvate (10 mM), but application of ATP-sensitive K+ channel blocker, glybenclamide (100 ?M), did not reverse the KCN-induced inhibition of myometrial contractions (n= 7). Furthermore, the inhibition of spontaneous myometrial contractions by KCN (0.5 mM, n=6) was reversed by the application of K+ channel blocker TEA (1 mM, n= 6). Conclusion: Results from this study indicate that K+ channels play a role, at least partially, in KCN-induced inhibition of myometrial contractions of rat and this inhibition may be reversed by pyruvate. Copyright © 2007 by Türkiye Klinikleri.
İzole siçan miyometriyumunda metabolik stres ve kasilabilme: Bikarbonat ve HEPES tamponu i?çeren kayit solüsyonlarinin kasilma yetene?i üzerine etkisi ve potasyum kanallarinin rolü
Keywords: Intermediate-conductance calcium-activated potassium channels; Myometrium